DIGITAL TRANSFORMATION AMONG WOMEN-LED MSMES DURING THE COVID-19 PANDEMIC IN KERALA - Rakhi Saratni K S; S Ramola Ponmalar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The COVID-19 pandemic brought unprecedented challenges to businesses worldwide, particularly Micro, Small, and Medium Enterprises (MSMEs). Women-led MSMEs in Kerala faced unique hurdles due to limited resources, market disruptions, and societal norms. However, the crisis also catalyzed a significant shift towards digital transformation. This study explores the impact of digital adoption on women-led MSMEs during the pandemic, focusing on the challenges, opportunities, and strategies employed to ensure business continuity and growth. The research investigates the extent to which women entrepreneurs in Kerala integrated digital tools for marketing, operations, and customer engagement. It examines the role of government initiatives, technological advancements, and community support in facilitating this transition. Key areas of focus include e-commerce adoption, digital payment systems, and the use of social media for business promotion. The study also identifies barriers to digital transformation, such as inadequate digital literacy, financial constraints, and limited access to technology. Through a combination of qualitative and quantitative methods, the study reveals how digital transformation enabled women entrepreneurs to expand their market reach, improve operational efficiency, and enhance customer satisfaction despite the pandemic’s economic challenges. It highlights inspiring success stories and best practices while addressing persistent challenges that require targeted interventions. The findings underline the critical role of digital transformation in fostering resilience and empowering women entrepreneurs in Kerala’s MSME sector. The study offers policy recommendations to enhance digital literacy, improve access to technology, and provide financial incentives for digital adoption. By spotlighting the intersection of gender, technology, and entrepreneurship, this research contributes valuable insights into building a more inclusive and robust business ecosystem in the post-pandemic era. The target respondents for the study are the Women-Led MSMEs in Kerala.110 people were chosen favourably for this investigation. Stratified random sampling was used to gather 110 respondents from Kerala in order to obtain the relevant data.